Solvent Recyclable Synthesis of Nitrogen‐Rich Nanotubes with Embedded CoFe Nanoparticles for Electrochemical Oxygen‐Involving Reactions. Issue 3 (27th January 2022) - Tang, Jialun; Tian, Shubo; Zhang, Yangyang; Sun, Kai; Xu, Shuhui; Zhou, Daojin; Sun, Xiaoming
Abstract : Polymerization followed by pyrolysis is an excellent method for synthesizing metal–nitrogen–carbon electrocatalysts, which have shown great potential in various application scenarios including water splitting, fuel cells, and metal–air batteries. However, the polymerization process usually uses a large amount of solvent that cannot be recycled, resulting in solvent waste, cost increase, and environmental pollution, which hinders its wide applications in industry. Inspired by the high polarity and polymerization of formamide (FA), CoFe nanoparticles on nitrogen–carbon nanotubes are synthesized by a FA‐sourced recycle strategy, in which the filtrate after one batch of synthesis will be used as solvent, carbon and nitrogen source for the next batch of synthesis, until the filtrate is consumed totally, verifying this procedure is a cost‐effective method and without any waste discharge. Besides, the catalysts prepared by each batch of recycle procedure exhibit outstanding and consistent oxygen reduction/evolution catalytic performance and satisfying cycle stability when used as an air electrode in a rechargeable zinc‐air battery. This work puts up a simple and clean method for the preparation of metal–nitrogen–carbon electrocatalysts for industrialized use. Abstract : N‐rich nanotubes with embedded CoFe nanoparticles are prepared by a formamide‐assisted filtrate‐recycled approach, in which formamide as solvent, carbon and nitrogen source, facilitates the dissolution of metal precursors and the carbonization for metal‐based nitrogen carbon material synthesis. The prepared electrocatalysts exhibit consistent bifunctional electrocatalytic performance regardless of experimental batches, verifying the high atom utilization efficiency.